Fast-pulsing LED-enhanced NMR: A convenient and inexpensive approach to increase NMR sensitivity - Yang, Hanming (J Chem Phys, 2019)
Low-concentration photochemically induced dynamic nuclear polarization (LC-photo-CIDNP) has recently emerged as a powerful technology for the detection of aromatic amino acids and proteins in solution in the low-micromolar to nanomolar concentration range. LC-photo-CIDNP is typically carried out in the presence of high-power lasers, which are costly and maintenance-heavy. Here, we show that LC-photo-CIDNP can be performed with light-emitting diodes (LEDs), which are inexpensive and much less cumbersome than lasers, laser diodes, flash lamps, or other light sources. When nuclear magnetic resonance (NMR) sample concentration is within the low-micromolar to nanomolar range, as in LC-photo-CIDNP, replacement of lasers with LEDs leads to no losses in sensitivity. We also investigate the effect of optical-fiber thickness and compare excitation rate constants of an Ar ion laser (488 nm) and a 466 nm LED, taking LED emission bandwidths into account. In addition, importantly, we develop a novel pulse sequence ((13)C RASPRINT) to perform ultrarapid LC-photo-CIDNP data collection. Remarkably, (13)C RASPRINT leads to 4-fold savings in data collection time. The latter advance relies on the fact that photo-CID nuclear hyperpolarization does not suffer from the longitudinal-relaxation recovery requirements of conventional NMR. Finally, we combine both the above improvements, resulting in facile and rapid (≈16 s–2.5 min) collection of 1 and 2D NMR data on aromatic amino acids and proteins in solution at nanomolar to low micromolar concentration.